A single-stage constant-power and optimal-efficiency double-sided LCC wireless battery charger - Yan, Jiabo; Aziz, Mohd Junaidi Bin Abdul; Idris, Nik Rumzi Nik; Sutikno, Tole (Institute of Advanced Engineering and Science, 2025)
This article proposes a novel single-stage double-sided LCC (DS-LCC) constant power (CP) wireless battery charger. The proposed CP charger uses a closedloop control in the secondary side with the active rectifier to make the DS-LCC charger achieve CP charging and optimal efficiency. Compared to previous work, the proposed CP wireless power transfer system does not involve any switch-controlled capacitor (SCC), does not require wireless communication, and can achieve optimal efficiency throughout the charging process. The proposed charger reduces cost and system complexity while improving efficiency. The proposed wireless charger is validated by simulation, and the efficiency remains between 94.44% and 94.52%, surpassing the previous work.